Motywacje przy podejmowaniu studiów wyższych ekonomicznych - Jarecki, Wojciech (Annales. Etyka w Życiu Gospodarczym, 2015)
Higher education should enable students to raise their qualifications, and particularlyacquire new knowledge, develop their interests, or learn to think critically. Asfor economics students, tertiary education should provide them with opportunity tofind and follow their career path. Having this in mind, the author of the presentpaper discusses factors contributing to economics students' involvement in raisingtheir qualifications. The main aim is to state why they have become less involvedin doing so, and particularly in acquiring new knowledge.